Prevalence and factors associated with antenatal depressive symptoms among women enrolled in Option B+ antenatal HIV care in Malawi: a cross-sectional analysis. (4th March 2019) - Harrington, Bryna J.; Pence, Brian W.; John, Mathias; Melhado, Caroline G.; Phulusa, Jacob; Mthiko, Bryan; Gaynes, Bradley N.; Maselko, Joanna; Miller, William C.; Hosseinipour, Mina C.
Abstract: Background : Option B+ has increased the number of pregnant women initiating antiretroviral therapy for HIV, yet retention in HIV care is sub-optimal. Retention may be affected by antenatal depression. However, few data exist on antenatal depression in this population. Aim : Describe the prevalence and factors associated with antenatal depression among Malawian women enrolled in Option B+. Method : At their first antenatal visit, women with HIV provided demographic and psychosocial information, including depression as measured with the locally validated Edinburgh Postnatal Depression Scale (EPDS). Prevalence ratios (PR) for factors associated with probable depression (EPDS ≥6) were estimated with log binomial regression. Results : 9.5% (95% CI: 7.5–11.9%) of women screened positive for current depression, and 46% self-reported a history of depression or anxiety. Women were more likely to screen positive for current depression if they reported a history of depression (adjusted PR: 2.42; 95% CI: 1.48–3.95) or had ever experienced intimate partner violence (1.77; 1.11–2.81). Having an unintended current pregnancy (1.78; 0.99–3.21), being unmarried (1.66; 0.97–2.84), or employed (1.56; 1.00–2.44) had potential associations with probable depression. Conclusions : Probable antenatal depression affected a notable proportion of women living with HIV, comparable to other global regions. Screening for antenatal depression in HIV care should be considered.